2014
DOI: 10.1016/j.schres.2014.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative electroencephalography as a biomarker for proneness toward developing psychosis

Abstract: The fully dimensional approach to the relationship between schizotypal personality traits and schizophrenia describes schizotypy as a continuum throughout the general population ranging from low schizotypy (LoS) and psychological health to high schizotypy (HiS) and psychosisproneness. However, no biological markers have yet been discovered that reliably quantify an individual's degree of schizotypy and/or psychosis. This study aimed to evaluate quantitative electroencephalographic (qEEG) measures of power spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…In the resting state, Fuggetta, Bennett et al (2014) reported decreased spontaneous power in subjects with high schizotypy (though this was not statistically significant), while Tcheslavski (2008) reported increased power and Tcheslavski and Beex (2010) reported increased phase synchrony.…”
Section: Schizotypymentioning
confidence: 80%
See 1 more Smart Citation
“…In the resting state, Fuggetta, Bennett et al (2014) reported decreased spontaneous power in subjects with high schizotypy (though this was not statistically significant), while Tcheslavski (2008) reported increased power and Tcheslavski and Beex (2010) reported increased phase synchrony.…”
Section: Schizotypymentioning
confidence: 80%
“…Eight studies examined gamma in relation to schizotypy, comprising a total of 223 participants (Table 5). Five studies (Vernon, Haenschel et al 2005, Tcheslavski 2008, Tcheslavski and Beex 2010, Fuggetta, Bennett et al 2014 divided healthy volunteers into two groups based on their scores on a schizotypy scale, 2 (Skosnik, Krishnan et al 2006, Kornmayer, Leicht et al 2015 correlated measures of gamma with schizotypy scores of healthy volunteers and one (Brenner, Sporns et al 2003) compared people with schizotypal personality disorder to healthy controls. The Schizotypy Personality Questionnaire (Raine 1991) was used to measure schizotypy in 7 studies (Vernon, Haenschel et al 2005, Skosnik, Krishnan et al 2006, Tcheslavski 2008, Tcheslavski and Beex 2010, Kornmayer, Leicht et al 2015, while Fuggetta, Bennett et al…”
Section: Schizotypymentioning
confidence: 99%
“…Previous studies have suggested that both the spectral power in the alpha band and the slowing of the alpha frequency peak are clinically and functionally relevant parameters in schizophrenia (Jin et al, 2000;Gaspar et al, 2011;Abeles and Gomez-Ramirez, 2014;Fuggetta et al, 2014). Thus, correlational analyses focusing on alpha power and Fig.…”
Section: Correlations With Clinical Variablesmentioning
confidence: 98%
“…Post-hoc tests showed significantly lower power in SZ relative to HC within this frequency band. Given the possibility of a slowing in spontaneous EC alpha peak frequency reported in prior studies (Jin, et al, 2000;Fuggetta, et al, 2014), the average frequency of individual peaks was evaluated ( Supplementary Fig. 2).…”
Section: Spontaneous Eyes-closed (Ec)mentioning
confidence: 99%
“…Electrophysiologically, the prediction can be investigated by analysing cross-frequency amplitude-amplitude coupling (AAC) [ 11 ], that is, correlations between signal amplitudes at two different frequencies f 1 and f 2 in the time-frequency spectrum. Empirical support for an increase in AAC has indeed been found in a number of studies and across various neurological conditions, both in comparison of patients to healthy controls (e.g., various conditions related to TCD [ 11 , 22 ], schizotypy [ 23 ]) and in pre-post intervention studies (e.g., various conditions related to TCD treated by central lateral thalamotomy [ 24 ]; phantom limb pain treated by deep brain stimulation [ 25 ]). However, in a study of obsessive-compulsive disorder, significant coupling between the delta (1–3 Hz) and beta (13–30 Hz) bands as well as between theta and beta was found only for the controls but not the patients [ 26 ].…”
Section: Introductionmentioning
confidence: 83%